PURWARUPA SISTEM PEMBERITAHUAN HALTE BUS TRANS JOGJAKARTA DENGAN OUTPUT AUDIO DAN DISPLAY BERBASIS MIKROKONTROLER ATEMEGA8535 - , CHANDRA ANGGARA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The prototype information system of Transjogja bus shelter has been made, this system is using IC RX-2B and TX-2B based on microcontroller that is designed to ease in giving information about name of Transjogja shelters. This system consists of IC RX-2B and TX-2B, IC ISD 2560, microcontroller and LCD. The location of Transjogja bus shelter will be displayed in LCD and sounded by speaker. The design of this system uses IC ISD 2560 that is used in microcontroller ATMega8535 recording series, IC RX-2B, TX-2B, and LCD 16x2. IC TX-2B as transmitter is designed as marker for each Transjogja bus shelter which is then sending the information to RX-2B (receiver), TX-2B has four outputs which provide different pulse frequency by 10 Meters outdoor communication maximum distance from the receiver. Whereas in IC RX-2B as receiver at once functions as server will receive the data and will be extended to microcontroller for the further process, the result of processing microcontroller data is displayed on LCD 16x2, the LCD will display Transjogja bus shelters location appropriate with the name of the shelter and be continued with sound output managed by IC ISD2560, the speaker will be sounded due to the location display on LCD.